Strategies against climate change from a sustainability approach in the educational sector of Jalcocotán - Mercado Burciaga , Ulises (Acta Universitaria, 2023)
One of the biggest current problems is climate change due to the concentration of greenhouse gases in the atmosphere produced by human activities. The objective of this research was to design strategies against climate change from a sustainability approach in order to contribute to decision-making in schools from Jalcocotán, aiming to reduce CO2 emissions associated with food consumption, transportation, and electricity consumption. To this end, CO2 emissions from food consumption, transportation, and electricity consumption were analyzed, the activity with the greatest impact was identified, and strategies were designed. Results show that the transfer to schools contributes with 73% of total CO2 emissions, food consumption with 24%, and electricity consumption with 3%. Finally, a reforestation and ecological mobility plan was implemented.